Alternations in markers of insulin resistance: HOMA-IR, HOMA-B, QUICKI, after dual therapy combination with telmisartan/amlodipine in prediabetic hypertensive patients. (11th May 2022) - Liontos, A; Papathanasiou, A; Biros, D; Papagiannopoulos, C; Tsourlos, S; Athanasiou, L; Veliani, C; Kolios, NG; Pappa, C; Zarachi, A; Christaki, E; Liberopoulos, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction-Purpose: The combination of telmisartan and amlodipine in tablet form indicated for patients whose arterial blood pressure cannot be fully managed with monotreatment. The purpose of this study was to investigate the effect of the fixed combination telmisartan/amlodipine 80/5mg per day on arterial pressure levels and the variation of HOMA-IR, HOMA-B and QUICKI values in patients with stage 2 hypertension (systolic blood pressure (SBP) 160-179 mmHg and/or diastolic blood pressure (DBP) 100-109 mmHg) and with prediabetes (IFG/IGT) before and after the 3-month treatment with the administration of the fixed combination. Methods: Data collected from 51 patients who have visited our outpatient clinic for lipid metabolism disorders during the period 2014-2018. 51 persons with BMI: 29.32 [27.37-31.65] (25 male, 16 female) had been randomized in the group for telmisartan/amlodipine 80/5mg per day. The median values for the study's sample in SBP and DBP were: 163[158-168] and 100[95-106] mmHg, respectively. Their somatometric and demographic characteristics were recorded in the beginning of the study and are presented on Table 1Α. Results: The results of the variations in SBP and DBP, as well as the variations in glucose, insulin, HOMA-IR, HOMA-B and QUICKI before and after the 3-month treatment are presented on Table 1B. Conclusions: From the sampled patients it can be observed that the 3-month treatment with telmisartan/amlodipine statistically significantly improved (p=0.005) the HOMA-IR values while improving fasting glucose and insulin levels. Finally, there was a statistically significant reduction in QUICKI values and a statistically insignificant reduction in HOMA-B.